Insurgent terrorism: intergroup relationships and the killing of civilians - Asal, Victor (Causes and consequences of terrorism, 2022)
Insurgent groups consist of individuals willing to organize and commit acts of terror to achieve their goals. By nature, they depend on public support, yet they sometimes target private civilians in addition to military personnel and government officials. This book examines insurgent embeddedness—the extent to which an insurgent group is enmeshed in relationships with the state, other insurgents, and the public—in order to understand why they attack civilians. Using Big Allied and Dangerous (BAAD) as the dataset, this book drills into civilian attacks in specific contexts, including schools, news media, and nonmilitary/nongovernment spaces designed for the general public. This book goes one step further, presenting in-depth analyses of intergroup alliances and rivalries, their changes and determinants over time, and the implications for several types of bloodshed against civilians. Insurgent Terrorism offers a comprehensive, modern approach for academics, students, and policy practitioners who seek to understand interorganizational relationships between insurgent organizations.